Reforming Tanzania's public sector assessment and future direction - Mutahaba, Gelase (Dar es Salaam Mkuki na Nyota, 2017)
In the last three decades, most African countries have embarked on comprehensive public sector reform programs. These have aimed at improving efficiency, accountability and transparency, for better delivery of public services and poverty reduction. Tanzania has, in addition, focused on tools, systems and processes in the Ministries, Departments and Agencies (MDAs) in order to remove the bottlenecks that have hindered effective public service delivery in the first place.
Includes bibliography
Keywords: Tanzania